Dynamics of Value Creation in Iranian Capital Market FinTechs: A Qualitative Analysis of Factors Affecting FinTech Valuation - Behzadi, Roghayeh; Rezaei, Nader; Fadaei, Mehdi; Babajafari , Rokhsareh (Digital Transformation and Administration Innovation, 2026)
This research aims to identify and explain the factors influencing the valuation of FinTech companies in the Iranian capital market and to propose a conceptual model. Given the accelerating pace of technological change and the increasing role of human capital, focusing on the underlying value-creation factors in the intangible assets of FinTechs within the capital market appears essential. The current study was conducted based on the interpretivist paradigm and an inductive approach. In terms of objective, this research is exploratory and developmental. Based on the data collection method, this research is descriptive-interpretive, carried out through semi-structured interviews. The research population included academic experts, experienced specialists, and managers of companies operating in the FinTech field. Purposive sampling was employed, reaching theoretical saturation with 12 participants. Documentary content analysis and interview analysis were used for data analysis. Research findings, based on prior studies and expert interview results, indicated that FinTech valuation in Iran goes beyond traditional financial variables and is heavily influenced by strategic and qualitative dynamics. The six main factors affecting valuation include: organizational and managerial factors, technological characteristics, financial and economic factors, legal, institutional, and regulatory factors, investor behavior, and strategic value derived from specific Iranian conditions. These findings emphasize the importance of shifting focus from the appraisal of tangible assets to the valuation of intangible and knowledge-based assets.